Hear our voices: Pre-service English Teachers’ Challenges and Expectations during Teaching Practice - Dwi Yumna Abdullah; Yazid Basthomi (Pascasarjana UM, 2020)
Abstract: Teaching practicum is one of the most fundamental and crucial stages in the teacher preparation program. The pre-service teacher readiness can be developed to become a qualified future teacher. This descriptive qualitative study is aimed to find the challenges and expectations of pre-service English teachers, mentor teachers, university supervisor, and the head of the teaching practice program. The findings indicated that pre-service teachers are challenged to improve their classroom management, strategies, and methods of teaching. The pre-service teachers, mentor teachers, and university supervisor are expected to gain benefits and successful school-university partnership.Keywords: challenges, expectations, pre-service english teacher, teaching practiceAbstrak: Praktek mengajar adalah salah satu tahap yang paling penting dan berpengaruh dalam program persiapan guru. Kesiapan praktikan dapat dikembangkan untuk menjadi guru masa depan yang berkualitas. Penelitian deskriptif kualitatif ini bertujuan untuk menemukan tantangan dan ekspektasi praktikan bahasa Inggris, guru pamong, dosen pembimbing, dan kepala program praktik mengajar. Temuan menunjukkan bahwa praktikan ditantang untuk meningkatkan manajemen kelas, strategi, dan metode pengajaran mereka. Para praktikan, guru pamong, dan dosen pembimbing diharapkan mendapatkan manfaat dan hubungan sekolah-universitas yang berhasil.Kata kunci: tantangan, ekspektasi, calon guru bahasa inggris, praktik mengajar